Can the carbon and nitrogen isotope values of offspring be used as a proxy for their mother's diet? Using foetal physiology to interpret bulk tissue and amino acid δ15N values. Issue 1 (24th July 2020) - Lübcker, Nico; Whiteman, John P; Newsome, Seth D; Millar, Robert P; de Bruyn, P J Nico
Abstract: The measurement of bulk tissue nitrogen (δ 15 N) and carbon isotope values (δ 13 C) chronologically along biologically inert tissues sampled from offspring can provide a longitudinal record of their mothers' foraging habits. This study tested the important assumption that mother–offspring stable isotope values are positively and linearly correlated. In addition, any change in the mother–offspring bulk tissues and individual amino acids that occurred during gestation was investigated. Whiskers sampled from southern elephant seal pups ( Mirounga leonina ) and temporally overlapping whiskers from their mothers were analyzed. This included n = 1895 chronologically subsampled whisker segments for bulk tissue δ 15 N and δ 13 C in total and n = 20 whisker segments for amino acid δ 15 N values, sampled from recently weaned pups ( n = 17), juvenile southern elephant seals (SES) < 2 years old ( n = 23) and adult female SES ( n = 17), which included nine mother–offspring pairs. In contrast to previous studies, the mother–offspring pairs were not in isotopic equilibrium or linearly correlated during gestation: the Δ 15 N and Δ 13 C mother–offspring offsets increased by 0.8 and 1.2‰, respectively, during gestation. The foetal bulk δ 15 N values were 1.7 ± 0.5‰ (0.9–2.7‰) higher than mothers' δ 15 N values before birth, while the foetal δ 13 C increased by 1.7‰ during gestation and were 1.0 ± 0.5‰ (0.0–1.9‰) higher than their mothers' δ 13 C at the end of pregnancy. The mother–offspring serine and glycine Δ 15 N differed by 4.3‰, while the foetal alanine δ 15 N values were 1.4‰ lower than that of their mothers during the third trimester of pregnancy. The observed mother–offspring δ 15 N differences are likely explained by shuttling of glutamate–glutamine and glycine–serine amongst skeletal muscle, liver, placenta and foetal tissue. Foetal development relies primarily on remobilized endogenous maternal proteinaceous sources. Researchers should consider foetal physiology when using offspring bulk tissue isotope values as biomarkers for the mother's isotopic composition as part of monitoring programmes.